Stainless steel cathode plate coating of electrolytic bath and preparation method of stainless steel cathode plate coating
Through the stainless steel cathode plates of the electrolytic grooves, coating specific powder materials on layers to change the electrode potential, so that nickel ions are prioritized, solving the problem of low nickel recovery efficiency and environmental pollution in existing technologies, and realized efficient and environmental protection Nickel recovery.
Patent Information
- Application Number
- CN202311272087.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-01-28
AI Technical Summary
The prior art has problems such as low treatment efficiency, low nickel content of the product, serious environmental pollution and low nickel recycling value when treating nickel-containing ferric chloride etching waste liquid.
By launching the powder of titanium titanium, titanium oxide, titanium titanium dioxide, titanium titanium titanium, diexide, silicon carbide, and silicon on the electrolytes of stainless steel cathode plates, change the electrode potential of the cathode plate, so that nickel ion priority is given priority The precipitation of hydrogen ions can be recovered by the high level of nickel.
It improves the treatment efficiency of nickel. The nickel recovery product is more than 70%, which has high economic value, and this method is environmentally friendly and friendly. It has no waste gas and avoids environmental pollution.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrolysis, and in particular to a coating of a stainless steel cathode plate of an electrolytic cell and a preparation method thereof. Background Art
[0002] Etching is widely used in various high-tech product fields such as integrated circuit lead frames, surface mount (SMT), encoder grating fluorescent display screen displays, microelectrodes, mask plates, integrated circuit cover plates, cathode ray tube shadow masks, solder paste screen printing boards, etc.
[0003] The ferric chloride etching method is widely used in various high-tech product fields such as integrated circuit lead frames, surface mount (SMT), encoder grating fluorescent display screen displays, grids, precision filters, microelectrodes, mask plates, integrated circuit cover plates, cathode ray tube shadow masks, solder paste screen printing plates, etc.
[0004] Ferric chloride solution has strong oxidizing properties. Under acidic conditions, it has a good corrosive effect on iron, nickel, and chromium. Therefore, it is widely used in metal etching. 3 Reduced to FeC1 by nickel stainless steel 2 At the same time, the metal nickel and chromium will be oxidized to Ni 2+ Cr 3+ During the etching process, as FeC1 3 The decrease in concentration and Fe 2+ As the concentration increases, the etching efficiency decreases, the etching surface of the product tends to be too rough, and the processing accuracy cannot meet the process requirements of integrated circuit lead frames, surface mount (SMT), encoder grating fluorescent display screens, etc. Therefore, a large number of used Ni containing about 3-5% 2+ , 3-8% Fe 2+ Ionic FeCl 3 The etching liquid is discharged in the form of waste liquid. If this waste liquid is discharged as hazardous waste without treatment, it will not only cause environmental pollution, but nickel ions have a strong carcinogenic effect. The wastewater discharge will infiltrate into the soil, produce enrichment and enter into crops, and eventually endanger human life and health. In addition, nickel itself is expensive, so the recycling and regeneration of nickel elements is of great significance to the economy and environmental protection.
[0005] At present, there are mainly the following methods for treating nickel-containing ferric chloride etching waste liquid: selective precipitation method, crystallization roasting method, metal reduction method, electrolytic reduction method, etc. However, each of these methods has different problems, as follows: 1. Other chemical reagents need to be introduced, such as hydrochloric acid and iron powder, which has high processing costs and high production labor intensity and is not suitable for large-scale processing; 2. Low processing efficiency and small nickel removal depth; 3. It is difficult to recycle the treated waste liquid; 4. Toxic gases such as chlorine and hydrogen chloride are produced during the treatment process, which pollute the environment. The resulting product is an iron-nickel mixture with a nickel content of only about 5-8%, which has no economic value.
[0006] Therefore, in view of the current situation, it is necessary to make technical improvements on the treatment of nickel-containing ferric chloride etching waste liquid. Summary of the invention
[0007] The purpose of the present invention is to provide a new coating material for the cathode plate of an electrolytic cell, and to change the electrode potential of the cathode stainless steel plate by coating the material on the cathode plate of the electrolytic cell, specifically by coating the material row by row in layers, so that nickel ions are precipitated preferentially over hydrogen ions, thereby achieving the purpose of high-grade recovery of metallic nickel from etching waste liquid.
[0008] Specifically, the present invention adopts the following technical solutions: A method for preparing a coating on a stainless steel cathode plate of an electrolytic cell comprises the following steps: Step 1: First, the surface of the stainless steel electrode plate is sandblasted; Step 2, then, the stainless steel electrode plate after sandblasting is degreased and derusted; Step 3, titanium carbide, titanium oxide, titanium diboride, silicon dioxide, silicon carbide and silicon are mixed according to a proportion, and then ball milled on a ball mill to obtain a mixture powder, while controlling the particle size of the mixture powder to be 300-400 mesh; Step 4, adding the above-mentioned mixture powder into a mixed solvent and mixing with the mixed solvent to prepare a slurry, and brushing the slurry on the surface of the stainless steel electrode plate treated in step 3, and controlling the thickness of the coating to be 0.1-0.2 mm; Step 5, finally, the coated stainless steel electrode plate is baked in a furnace at 600-800° C. for 30-50 minutes, and then cooled to complete the treatment of the stainless steel cathode plate, and a coating is obtained on the surface of the stainless steel cathode plate.
[0009] Further preferably, in step 3, the mass ratios of titanium carbide, titanium oxide, titanium diboride, silicon dioxide, silicon carbide and silicon in the mixed powder are 30-50%, 20-40%, 5-15%, 2-10%, 2-8% and 1-5%.
[0010] Further preferably, in step 4, the coating preparation step is: preparing a slurry with the ball-milled mixture powder and a mixed solvent, the mixed solvent specifically being tetrahydrofuran and castor oil, ethanol, and triethyl phosphate, and the volume ratio of each component is 40-60:20-30:10-15:5-10.
[0011] Further preferably, in step 1, the sandblasting treatment is specifically: using 30-50 mesh coarse sand and 70-90 mesh fine sand for low-pressure sandblasting at 0.1-0.2 MPa and high-pressure sandblasting at 0.5-0.6 MPa, respectively, and the treatment time is 10-15S.
[0012] Further preferably, in step 2, The sandblasted stainless steel electrode plate is degreased in an alkaline degreasing solution at 70-80°C for 5-10 minutes, then pickled with dilute hydrochloric acid for 5 minutes, washed with deionized water, and dried with cold air at 5-25°C.
[0013] The stainless steel cathode plate painted or coated is used for electrolysis process to treat etching liquid. In the process of treating etching waste liquid, the electrode is not only a current conduction carrier, but also affects the electrode potential of the electrode reaction. The selection of electrode coating material directly affects the current conduction efficiency and reaction voltage of the electrode. In the current electrolysis device, the technical bottleneck is that the standard electrode potential of cathode hydrogen ions is greater than the standard electrode potential of nickel ions, making it difficult for nickel to be reduced and reused from the high-acidity etching waste liquid.
[0014] In the current electrolytic recycling process, the cathode chemical reaction is: 2H + + 2e → H 2 ; Ni 2 + +2e - → You.
[0015] According to the Nernst equation, when the temperature is 40℃, ω(Ni 2+ )=1.4 g / L, Ni 2+ The precipitation potential is: .
[0016] When the acidity is N=2, the actual precipitation potential of hydrogen ions on the cathode is: .
[0017] Since the electrode potential of hydrogen ions on the cathode is much greater than that of nickel ions, after an external voltage is applied to both ends of the electrolytic cell, hydrogen ions will be discharged first to generate hydrogen gas, making it difficult for nickel ions to precipitate from the etching waste liquid.
[0018] In the present invention, titanium carbide, silicon carbide, silicon, titanium diboride, silicon dioxide, and titanium oxide powder materials are coated layer by layer to change the electrode potential of the cathode stainless steel plate, effectively reduce the electrode potential of the cathode plate, increase the overpotential of hydrogen, and make nickel precipitate before hydrogen, thereby achieving the recovery and utilization of metallic nickel from the etching waste liquid.
[0019] Specifically, in order to balance the properties of the coating, the inventor creatively used a combination of titanium carbide, silicon carbide, silicon, titanium diboride, silicon dioxide, titanium oxide and other conductors and semiconductors, thereby ensuring that the coating not only has the corresponding conductivity, but also has a certain anti-corrosion effect. Such a combination can obtain an excellent electrode potential, which enables the generation of metallic nickel on the cathode plate.
[0020] Compared with the prior art, the present invention has the following beneficial effects: Solid powder is used to prepare slurry with liquid solvent to treat the electrode plate, which can be reused, has a long service life and low raw material cost; The nickel treatment efficiency is high, and the nickel treatment is synchronized in the electrolytic cell to avoid the problem of heavy workload caused by the accumulation of etching waste liquid; Through the immediate treatment of etching waste liquid, the waste liquid can be recycled and reused, saving costs; The overall treatment process does not generate waste gas, is environmentally friendly, and avoids pollution to the environment; The nickel precipitation is relatively concentrated, which is conducive to the collection and reuse of nickel, thereby increasing its economic value. DETAILED DESCRIPTION
[0021] Representative embodiments will now be further refined. It should be understood that the following description is not intended to limit the embodiments to a preferred embodiment. On the contrary, it is intended to cover alternatives, modifications and equivalents that may be included in the essence and scope of the embodiments defined by the appended claims.
[0022] The present invention provides a method for surface coating treatment of a stainless steel cathode plate, and the overall scheme is as follows: Step 1, first, the surface of the stainless steel electrode plate is sandblasted; 30-50 mesh coarse sand and 70-90 mesh fine sand are used for low-pressure sandblasting at 0.1-0.2 MPa and high-pressure sandblasting at 0.5-0.6 MPa, respectively, and the treatment time is 10-15S.
[0023] Step 2, then, degreasing and derusting the sandblasted stainless steel electrode plate; degreasing the sandblasted stainless steel electrode plate in an alkaline degreasing solution at 70-80°C for 5-10 minutes, then pickling it with dilute hydrochloric acid for 5 minutes, then washing it with deionized water, and then drying it with cold air at 5-25°C.
[0024] Step 3, titanium carbide, titanium oxide, titanium diboride, silicon dioxide, silicon carbide and silicon are mixed according to proportion, and then ball milled on a ball mill to obtain a mixture powder, and at the same time, the particle size of the mixture powder is controlled to be 300-400 mesh; the mass ratios of titanium carbide, titanium oxide, titanium diboride, silicon dioxide, silicon carbide and silicon in the mixture powder are 30-50%, 20-40%, 5-15%, 2-10%, 2-8% and 1-5%.
[0025] Step 4, adding the above-mentioned mixture powder into a mixed solvent and mixing with the mixed solvent to prepare a slurry, and then brushing the slurry on the surface of the stainless steel electrode plate treated in step 3, and controlling the thickness of the coating to be 0.1-0.2mm; specifically: the ball-milled mixture powder is prepared into a slurry with a mixed solvent, and the mixed solvent is specifically tetrahydrofuran and castor oil, ethanol, and triethyl phosphate, and the volume ratio of each component is 40-60:20-30:10-15:5-10.
[0026] Step 5, finally, the coated stainless steel electrode plate is baked in a furnace at 600-800° C. for 30-50 minutes, and then cooled to complete the treatment of the stainless steel cathode plate, and a coating is obtained on the surface of the stainless steel cathode plate.
[0027] Based on the above scheme, the applicant verified it through specific actual examples.
[0028] Embodiment 1: First, a stainless steel cathode plate with a coating is prepared by coating the surface of the stainless steel cathode plate according to the above method; specifically: Step 1, first, the surface of the stainless steel electrode plate is sandblasted; 30-mesh coarse sand and 90-mesh fine sand are used for low-pressure sandblasting at 0.1-0.2 MPa and high-pressure sandblasting at 0.5-0.6 MPa, respectively, and the treatment time is 10 seconds.
[0029] Step 2, then, degreasing and derusting the sandblasted stainless steel electrode plate; degreasing the sandblasted stainless steel electrode plate in an alkaline degreasing solution at 70°C for 5 minutes, then pickling it with dilute hydrochloric acid for 5 minutes, then washing it with deionized water, and then drying it with cold air at 25°C.
[0030] Step 3, titanium carbide, titanium oxide, titanium diboride, silicon dioxide, silicon carbide and silicon are mixed in proportion, and then ball milled on a ball mill to obtain a mixture powder, and at the same time, the particle size of the mixture powder is controlled to be 300-400 mesh; the mass ratios of titanium carbide, titanium oxide, titanium diboride, silicon dioxide, silicon carbide and silicon in the mixture powder are 30%, 32%, 15%, 10%, 8% and 5%.
[0031] Step 4, adding the above-mentioned mixture powder into a mixed solvent and mixing with the mixed solvent to prepare a slurry, and then brushing the slurry on the surface of the stainless steel electrode plate treated in step 3, and controlling the thickness of the coating to 0.1 mm; specifically: the ball-milled mixture powder is prepared into a slurry with a mixed solvent, and the mixed solvent is specifically tetrahydrofuran and castor oil, ethanol, and triethyl phosphate, and the volume ratio of each component is 40:30:10:5.
[0032] Step 5, finally, the coated stainless steel electrode plate is baked in a furnace at 600° C. for 30 minutes, and then cooled to complete the treatment of the stainless steel cathode plate, and a coating is obtained on the surface of the stainless steel cathode plate.
[0033] Embodiment 2: First, a stainless steel cathode plate with a coating is prepared by coating the surface of the stainless steel cathode plate according to the above method; specifically: Step 1, first, the surface of the stainless steel electrode plate is sandblasted; 50 mesh coarse sand and 90 mesh fine sand are used for low-pressure sandblasting at 0.1-0.2 MPa and high-pressure sandblasting at 0.5-0.6 MPa, respectively, and the treatment time is 15 seconds.
[0034] Step 2, then, degreasing and derusting the sandblasted stainless steel electrode plate; degreasing the sandblasted stainless steel electrode plate in an alkaline degreasing solution at 80°C for 10 minutes, then pickling it with dilute hydrochloric acid for 5 minutes, then washing it with deionized water, and drying it with cold air at 10°C.
[0035] Step 3, titanium carbide, titanium oxide, titanium diboride, silicon dioxide, silicon carbide and silicon are mixed in proportion, and then ball milled on a ball mill to obtain a mixture powder, and at the same time, the particle size of the mixture powder is controlled to be 300-400 mesh; the mass ratios of titanium carbide, titanium oxide, titanium diboride, silicon dioxide, silicon carbide and silicon in the mixture powder are 50%, 40%, 5%, 2%, 2% and 1%.
[0036] Step 4, adding the above-mentioned mixture powder into a mixed solvent and mixing with the mixed solvent to prepare a slurry, and then brushing the slurry on the surface of the stainless steel electrode plate treated in step 3, and controlling the thickness of the coating to be 0.1-0.2mm; specifically: the ball-milled mixture powder is prepared into a slurry with a mixed solvent, and the mixed solvent is specifically tetrahydrofuran and castor oil, ethanol, and triethyl phosphate, and the volume ratio of each component is 60:20:15:5.
[0037] Step 5, finally, the coated stainless steel electrode plate is baked in a furnace at 700° C. for 40 minutes, and then cooled to complete the treatment of the stainless steel cathode plate, and a coating is obtained on the surface of the stainless steel cathode plate.
[0038] Embodiment 3: First, a stainless steel cathode plate with a coating is prepared by coating the surface of the stainless steel cathode plate according to the above method; specifically: Step 1, first, the surface of the stainless steel electrode plate is sandblasted; 50-mesh coarse sand and 70-mesh fine sand are used for low-pressure sandblasting at 0.1-0.2 MPa and high-pressure sandblasting at 0.5-0.6 MPa, respectively, and the treatment time is 15 seconds.
[0039] Step 2, then, degreasing and derusting the sandblasted stainless steel electrode plate; degreasing the sandblasted stainless steel electrode plate in an alkaline degreasing solution at 70-80°C for 8 minutes, then pickling it with dilute hydrochloric acid for 5 minutes, then washing it with deionized water, and drying it with cold air at 5°C.
[0040] Step 3, titanium carbide, titanium oxide, titanium diboride, silicon dioxide, silicon carbide and silicon are mixed according to proportion, and then ball milled on a ball mill to obtain a mixture powder, and at the same time, the particle size of the mixture powder is controlled to be 300-400 mesh; the mass ratios of titanium carbide, titanium oxide, titanium diboride, silicon dioxide, silicon carbide and silicon in the mixture powder are 45%, 20%, 15%, 10%, 5% and 5%.
[0041] Step 4, adding the above-mentioned mixture powder into a mixed solvent and mixing with the mixed solvent to prepare a slurry, and then brushing the slurry on the surface of the stainless steel electrode plate treated in step 3, and controlling the thickness of the coating to be 0.1-0.2mm; specifically: the ball-milled mixture powder is prepared into a slurry with a mixed solvent, and the mixed solvent is specifically tetrahydrofuran and castor oil, ethanol, and triethyl phosphate, and the volume ratio of each component is 60:20:10:5.
[0042] Step 5, finally, the coated stainless steel electrode plate is baked in a furnace at 600-800° C. for 30-50 minutes, and then cooled to complete the treatment of the stainless steel cathode plate, and a coating is obtained on the surface of the stainless steel cathode plate.
[0043] The stainless steel cathode plates prepared in Examples 1 to 3 were applied in actual production and used as cathode plates of electrolytic cells for actual miniaturized production operations.
[0044] Comparative Example 1: A stainless steel cathode plate without coating was selected.
[0045] The cathode plates prepared in Examples 1-3 and the cathode plate in Comparative Example 1 were subjected to simulated production operation using the stainless steel cathode plate as the cathode plate of the electrolytic cell in the same operating environment.
[0046] Through operation, the cathode plates of Examples 1-3 can produce a mixture containing nickel, and the nickel content can reach more than 70%, which has considerable economic value. However, the untreated electrode plate in Comparative Example 1 has a nickel content of less than 5% in the generated mixture, which has basically no economic value.
[0047] The nickel content of the nickel-containing mixture of Example 1-Example 3 is as follows: Nickel content (mass)% Example 1 78.2 Example 2 76.8 Example 3 77.6 The cathode plates of Examples 1-3 do not require the introduction of other chemical reagents during operation and are very suitable for large-scale processing. The processing efficiency is low and nickel in the etching waste liquid does not need to be removed. Not only can the treated waste liquid be recycled, but the resulting mixture has a high nickel content and has very good economic value.
[0048] It is obvious to those skilled in the art that certain modifications, combinations and variations can be made based on the above teachings.
Claims
1. A method for preparing a coating of a stainless steel cathode plate of an electrolytic cell, characterized in that: The following steps are involved: Step 1: First, the surface of the stainless steel electrode plate is sandblasted; Step 2, then, the stainless steel electrode plate after sandblasting is degreased and derusted; Step 3, titanium carbide, titanium oxide, titanium diboride, silicon dioxide, silicon carbide and silicon are mixed according to a proportion, and then ball milled on a ball mill to obtain a mixture powder, while controlling the particle size of the mixture powder to be 300-400 mesh; Step 4, adding the above-mentioned mixture powder into a mixed solvent and mixing with the mixed solvent to prepare a slurry, and brushing the slurry on the surface of the stainless steel electrode plate treated in step 3, and controlling the thickness of the coating to be 0.1-0.2 mm; Step 5, finally, the coated stainless steel electrode plate is baked in a furnace at 600-800° C. for 30-50 minutes, and then cooled to complete the treatment of the stainless steel cathode plate, and a coating is obtained on the surface of the stainless steel cathode plate.
2. The method for preparing a coating of a stainless steel cathode plate of an electrolytic cell according to claim 1, characterized in that: In step 3, the mass ratios of titanium carbide, titanium oxide, titanium diboride, silicon dioxide, silicon carbide and silicon in the mixed powder are 30-50%, 20-40%, 5-15%, 2-10%, 2-8% and 1-5%.
3. The method for preparing a coating of a stainless steel cathode plate of an electrolytic cell according to claim 2, characterized in that: In the step 3, the ratios of titanium carbide, titanium oxide, titanium diboride, silicon dioxide, silicon carbide and silicon in the mixture are 30-50%, 20-40%, 5-15%, 4-10%, 3-6% and 1-5%.
4. The method for preparing a coating of a stainless steel cathode plate of an electrolytic cell according to claim 1, characterized in that: In the step 4, specifically, the ball-milled mixture powder and a mixed solvent are prepared into a slurry, the mixed solvent specifically being tetrahydrofuran, castor oil, ethanol, and triethyl phosphate, and the volume ratio of each component is 40-60:20-30:10-15:5-10.
5. The method for preparing a coating of a stainless steel cathode plate of an electrolytic cell according to claim 1, characterized in that: In step 1, the sandblasting treatment is specifically as follows: using 30-50 mesh coarse sand and 70-90 mesh fine sand to perform low-pressure sandblasting treatment at 0.1-0.2 MPa and high-pressure sandblasting treatment at 0.5-0.6 MPa, respectively, and the treatment time is 10-15 seconds.
6. The method for preparing a coating of a stainless steel cathode plate of an electrolytic cell according to claim 1, characterized in that: In step 2, The sandblasted stainless steel electrode plate is degreased in an alkaline degreasing solution at 70-80°C for 5-10 minutes, then pickled with dilute hydrochloric acid for 5 minutes, washed with deionized water, and dried with cold air at 5-25°C.
7. A stainless steel cathode plate coating for an electrolytic cell prepared by the preparation method according to any one of the above claims.